Evolutionary Stability in Bargaining with an Asymmetric Breakdown Point - Pär Torstensson (Lund University, School of Economics and Management, Department of Economics, 2005)
We study an asymmetric two-player bargaining game with risk of breakdown and no discounting. We characterize the modified evolutionarily stable strategies (MESS) by modelling strategies as automata. Payoff and complexity considerations are taken in the automata-selection process. We show that a MESS exists in the bargaining game and that agreement is reached immediately. It turns out that in the search for evolutionary foundation, we find support for all partitions that assigns the positive breakdown utility x or more to the player with the higher breakdown utility, given that it exceeds half the surplus.
Keywords: C72; C73; C78; 330; Modified evolutionary stable strategies; bargaining; automata; asymmetric breakdown point.